2003
DOI: 10.17660/actahortic.2003.597.31
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Some Medicinal Plant Extracts Against Candida Albicans and Cryptococcus Neoformans

Abstract: The ethanol extracts of clove (Eugenia caryophyllus Bullock & Harrison) and sweet flag (Acorus calamus Linn.) were investigated for their antifungal activity in comparison with eugenol and amphotericin B (AmB) by using the National Committee for Clinical Laboratory Standards (NCCLs) M27-P broth microdilution method. Two medicinal plant extracts, eugenol and amphotericin B were used to determine their minimum inhibitory concentrations (MICs) and minimum fungicidal concentrations (MFCs) against 28 clinical isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…For example, in an analysis by Thirach et al, the antifungal activity of an ethanol extract of Acorus calamus was assessed against 28 clinical isolates of Candida albicans using a broth microdilution technique. The MIC was identified as 28800 ± 16320 mg/l and in this setting Acorus calamus was interpreted as being a potential fungistatic agent (Thirach et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in an analysis by Thirach et al, the antifungal activity of an ethanol extract of Acorus calamus was assessed against 28 clinical isolates of Candida albicans using a broth microdilution technique. The MIC was identified as 28800 ± 16320 mg/l and in this setting Acorus calamus was interpreted as being a potential fungistatic agent (Thirach et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…These plants were chosen based on either traditional usage suggestive of antifungal activity or previous studies that have demonstrated antifungal properties using alcohol extracts (McCutcheon et al, 1994;Jones et al, 2000;Filipowicz et al, 2003;Thirach et al, 2003). The antifungal activity of a commercial preparation of Melaleuca alternifolia (tea tree) oil was also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…albicans 100 mg/mL (Hassawi and Kharma, 2006) Achillea fragantissima C. albicans 150 mg/mL (Hassawi and Kharma, 2006) Acorus calamus C. albicans 28.80 mg/mL (Thirach et al, 2003) Adiantum capillus veneris C. albicans 1 mg/mL * (Ishaq et al, 2014) Allium cepa C. albicans 10 mg/mL * (Doddanna et al, 2013) Allium sativum C. albicans 1 mg/mL * (Wong and Tsang, 2009) Anthemis pseudocotula C. albicans 150 mg/mL (Hassawi and Kharma, 2006) Artemisia herba-alba C. albicans 100 mg/mL (Hassawi and Kharma, 2006) Ballota undulate C. albicans 25 mg/mL (Hashem, 2011) Camellia sinensis C. albicans 10 mg/mL * (Doddanna et al, 2013) Capparis spinosa C. albicans 100 mg/mL * (Mandeel and Taha, 2005) Capsicum annum C. albicans 17.5 mg/mL (Ertürk, 2006) Cassia alata C. albicans 5.60 mg (Timothy et al, 2012) Cassia siamea C. albicans 100 mg/mL C. glabrata 100 mg/mL C. guilliermondii 100 mg/mL C. krusei 100 mg/mL C. parapsilosis 100 mg/mL C. tropicalis 100 mg/mL Caulerpa scalpelliformis C. albicans 100 mg/mL C. glabrata 100 mg/mL C. guilliermondii 100 mg/mL C. krusei 100 mg/mL C. parapsilosis 100 mg/mL C. tropicalis 100 mg/mL …”
Section: Achillea Biebersteiniimentioning
confidence: 99%
“…The antifungal effects of many organic and natural compounds have been studied against pathogenic fungi [25][26][27][28][29][30][31][32][33][34]. According to the literature, eugenol has antifungal activities against C. neoformans, C. albicans, and A. parasiticus [20,32,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%